Military-National Defense Education in Secondary Schools (2): Pedagógusképzések, katonai szakközépiskolák a honvédelmi-katonai nevelés szolgálatában (Training and Practice : Journal of Educational Sciences, 2012)
The introductory part of the No. 190 law of 2011 about National Public Education emphasis the need for educating the growing generation patriots. Patriotic education has not been present since then, it has a longer history. We may remember of several events from literature and history which prove that Hungarians have always paid attention to educate young men who would protect the country. The history of military schools for the purpose of training future soldiers dates back to the 1850s. In the historical researches these 150 years are usually divided into 3 periods. Military schools have had a rather turbulent history and they suffered much from the changes of history. They were frequently reorganized, closed, re-opened, and training and raising methods were also changed many times. Still. these in This study presents military secondary schools and teacher trainings‘ stitutes had much success, and many graduates enioyed great careers.This study presents military secondary schools and teacher trainings.